Validity and reliability of the Dutch translation of the VISA-P questionnaire for patellar tendinopathy - Zwerver, Johannes (BioMed Central, 2009)
BACKGROUND: The VISA-P questionnaire evaluates severity of symptoms, knee function and ability to play sports in athletes with patellar tendinopathy. This English-language self-administered brief patient outcome score was developed in Australia to monitor rehabilitation and to evaluate outcome of clinical studies. Aim of this study was to translate the questionnaire into Dutch and to study the reliability and validity of the Dutch version of the VISA-P. METHODS: The questionnaire was translated into Dutch according to internationally recommended guidelines. Test-retest reliability was determined in 99 students with a time interval of 2.5 weeks. To determine discriminative validity of the Dutch VISA-P, 18 healthy students, 15 competitive volleyball players (at-risk population), 14 patients with patellar tendinopathy, 6 patients who had surgery for patellar tendinopathy, 17 patients with knee injuries other than patellar tendinopathy, and 9 patients with symptoms unrelated to their knees completed the Dutch VISA-P. RESULTS: The Dutch VISA-P questionnaire showed satisfactory test-retest reliability (ICC = 0.74). The mean (± SD) VISA-P scores were 95 (± 9) for the healthy students, 89 (± 11) for the volleyball players, 58 (± 19) for patients with patellar tendinopathy, and 56 (± 21) for athletes who had surgery for patellar tendinopathy. Patients with other knee injuries or symptoms unrelated to the knee scored 62 (± 24) and 77 (± 24). CONCLUSION: The translated Dutch version of the VISA-P questionnaire is equivalent to its original version, has satisfactory test-retest reliability and is a valid score to evaluate symptoms, knee function and ability to play sports of Dutch athletes with patellar tendinopathy.